H2 haplotype at chromosome 17q21.31 protects against childhood sexual abuse-associated risk for alcohol consumption and dependence - Nelson, Elliot C. (2010)
Animal research supports a central role for corticotropin releasing factor (CRF) in actions of ethanol on brain function. An examination of alcohol consumption in adolescents reported a significant genotype × environment (G × E) interaction involving rs1876831, a CRHR1 polymorphism, and negative events. CRHR1 and at least 4 other genes are located at 17q21.31 in an extremely large block of high linkage disequilibrium resulting from a local chromosomal inversion; the minor allele of rs1876831 is contained within the H2 haplotype. Here we examine whether G × E interactions involving this haplotype and childhood sexual abuse (CSA) are associated with risk for alcohol consumption and dependence in Australian participants (N=1128 respondents from 476 families) of the Nicotine Addiction Genetics project. Telephone interviews provided data on DSM-IV alcohol dependence diagnosis and CSA and enabled calculation of lifetime alcohol consumption factor score (ACFS) from 4 indices of alcohol consumption. Individuals reporting a history of CSA had significantly higher ACFS and increased risk for alcohol dependence. A significant G × E interaction was found for ACFS involving the H2 haplotype and CSA (p<0.017). A similar G × E interaction was associated with protective effects against alcohol dependence risk (odds ratio 0.42; 95%CI 0.20 – 0.89). For each outcome, no significant CSA-associated risk was observed in H2 haplotype carriers. These findings support conducting further investigation of the H2 haplotype to determine the gene(s) responsible. Our results also suggest that severe early trauma may prove to be an important clinical covariate in the treatment of alcohol dependence.